2018
DOI: 10.1177/1087054718797428
|View full text |Cite
|
Sign up to set email alerts
|

Attention in Children With Autism Spectrum Disorder and the Effects of a Mindfulness-Based Program

Abstract: Trend effects of the MBP on the attention systems of children with ASD were revealed, as well as minor differences between children with ASD and TD children in their attention systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 35 publications
1
24
0
Order By: Relevance
“…Although reaction times tend to be similar in ASD and TD individuals, there is some evidence that ASD individuals show significantly reduced accuracy on incongruent trials relative to congruent trials, resulting in larger accuracy difference scores. Mutreja et al (2016) reported this effect in children (ages 5-11) using the ANT-C; a similar finding that did not reach statistical significance was reported in a larger sample of slightly older group of individuals aged 8-23 (Ridderinkhof et al 2018). Using the ANT-R, Fan et al (2012) demonstrated poorer executive control accuracy in adults with ASD; further, they found that less accurate performance on the flanker component of the task was associated with reduced activation in the anterior cingulate cortex and more severe language and communication symptoms in the ASD group.…”
Section: Executive Controlmentioning
confidence: 65%
See 2 more Smart Citations
“…Although reaction times tend to be similar in ASD and TD individuals, there is some evidence that ASD individuals show significantly reduced accuracy on incongruent trials relative to congruent trials, resulting in larger accuracy difference scores. Mutreja et al (2016) reported this effect in children (ages 5-11) using the ANT-C; a similar finding that did not reach statistical significance was reported in a larger sample of slightly older group of individuals aged 8-23 (Ridderinkhof et al 2018). Using the ANT-R, Fan et al (2012) demonstrated poorer executive control accuracy in adults with ASD; further, they found that less accurate performance on the flanker component of the task was associated with reduced activation in the anterior cingulate cortex and more severe language and communication symptoms in the ASD group.…”
Section: Executive Controlmentioning
confidence: 65%
“…Furthermore, using fMRI, they found that alerting errors were associated with reduced brain activity in the medial frontal gyri and caudate. As with orienting network scores, some research reported no significant group differences in alerting networks in ASD (Ip et al 2017;Mutreja et al 2016;Ridderinkhof et al 2018;Samyn et al 2017).…”
Section: Alertingmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this has been found to be effective in TD students (153), the effectiveness for individuals with ASD has had mixed reports. Juliano et al (154) implemented an 8-week school-based mindfulness program with 24 students with ASD and found significant improvements in response inhibition and overall selective attention; however, Ridderinkhof et al (155) failed to demonstrate a significant beneficial effect of the program, although showed trends suggesting improvement in orienting and executive function.…”
Section: Attention-targeted Interventionsmentioning
confidence: 99%
“…As a result of mindfulness interventions, a person learns to direct their attention internally and avoid the “automatic pilot” that takes over the brain when stressed (Cachia et al, 2016 ). Some research exists with the use of modifications of mindfulness interventions (EASE, MyMind) to improve emotional regulation, impulse control, emotional acceptance (Conner & White, 2018 ; Conner et al, 2019 ; Salem-Guirgis et al, 2019 ), anxiety and rumination (Spek et al, 2013 ), quality of life (Ridderinkhof et al, 2018 ), attention (Ridderinkhof et al, 2020 ); and aggression (Singh et al, 2011 ). While some studies did modify the mindfulness intervention to decrease the use of metaphors and shorter sessions for people with autism (Conner & White, 2018 ; Kiep et al, 2015 ; Sizoo & Kuiper, 2017 ), it is unclear what improvement these modifications made for participants.…”
Section: Introductionmentioning
confidence: 99%